2019
DOI: 10.1186/s12888-019-2052-4
|View full text |Cite
|
Sign up to set email alerts
|

The burden, support and needs of primary family caregivers of people experiencing schizophrenia in Beijing communities: a qualitative study

Abstract: Background Family caregivers play crucial roles in taking care of people experiencing schizophrenia in the community. The burdens on and needs of caregivers of these patients should be emphasized. This study aimed to explore the perspective of family caregivers of people experiencing schizophrenia in the communities of Beijing in terms of the burdens of care and the acquisition and further need for support in order to provide guidance to health care providers regarding how to target therapeutic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
102
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(108 citation statements)
references
References 36 publications
2
102
1
3
Order By: Relevance
“…Previous studies have found that persons living with schizophrenia who were repeatedly hospitalized increased the burden on their families (33). Despite a better public understanding of schizophrenia in recent years, schizophrenia is still widely regarded as shameful for the patients' families and by the Chinese public (34,35). With the increase in the number of hospitalizations, the stigma around the patients and their families will strengthen (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that persons living with schizophrenia who were repeatedly hospitalized increased the burden on their families (33). Despite a better public understanding of schizophrenia in recent years, schizophrenia is still widely regarded as shameful for the patients' families and by the Chinese public (34,35). With the increase in the number of hospitalizations, the stigma around the patients and their families will strengthen (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…There could be support groups for caregivers run by social workers or health care professionals; education or sharing sessions with physicians on typical symptoms; regular home visits and establishment of day nursing/care or respite care to meet the needs of schizophrenia patients and relieve the burden of main informal caregivers. Sufficient resources should be allocated to vocational training and supported employment for patients who were in non-severe situation or in stable phase [27].…”
Section: Discussionmentioning
confidence: 99%
“…Although the government provided multi-channel resources for patients with schizophrenia and their families, the awareness and utilization of social supports were not optimistic. The underlying reasons might be: (1) the workforce of rehabilitation and social care professionals in China was insu cient [22]; (2) funding and other support from national and social institutions for mental illness were limited, and burdensome application procedures and unperfect quota allocations impaired the accessibility of various types of support [23]; (3) stigma and discrimination from the public and even mental health professionals [24,25], and low insurance coverage with high treatment fees created barriers to mental health service utilization [26]; (4) the mutual support groups and psychological counselling provided for caregivers were often considered super cial and impractical [27].…”
Section: Discussionmentioning
confidence: 99%